Conceptual Design of an Aircraft Using Hydrogen in a Dual-Fuel Configuration - Kadijk, M.G. (TU Delft, 2026)
The aviation sector faces increasing pressure to significantly reduce its climate impact. Particularly in the medium-range narrowbody aircraft segment, which accounts for a large share of global passenger traffic and emissions, large gains can be made. While hydrogen propulsion offers the potential for zero in-flight CO2 emissions, its implementation is challenged by volumetric storage penalties, operational limitations and infrastructure development. A dual-fuel aircraft concept, capable of operating on both liquid hydrogen and kerosene or sustainable aviation fuel (SAF), may provide a transitional solution that balances environmental benefits with operational flexibility. While previous studies into dual-fuel propulsion concepts showed the potential to reduce CO2 emissions, a research gap was identified in the development of a conceptual aircraft design method employing sequential dual-fuel use throughout the mission. This thesis investigates the impact of implementing a dual-fuel propulsion system using hydrogen and kerosene (or SAF replacement) on the design and performance of a medium-range narrowbody tube-and-wing turbofan aircraft. A parametric conceptual design model is developed using Python and the commercial ParaPy Python package, incorporating preliminary aircraft sizing, hydrogen tank structural and thermal modelling, aerodynamic analysis, engine performance modelling, mission analysis and well-to-wake energy and emission evaluation. Several fuel-use scenarios are evaluated, including full kerosene, full hydrogen, hydrogen-kerosene combinations, and varying fuel splits during cruise, for design ranges of 2500 km and 5000 km. The results show that introducing dual-fuel capability mainly affects aircraft design through an increase in fuselage length due to hydrogen tank integration, with this effect being more pronounced at 5000 km than at 2500 km range. Across both ranges, increasing hydrogen use reduces total fuel weight, but increases operational empty weight, resulting in only small changes in maximum take-off weight due to these counteracting effects. Dual-fuel operation partially mitigates the fuselage length and passenger capacity penalties observed for full-hydrogen configurations at both ranges. Although tank-to-wake CO2 emissions decrease with increasing hydrogen use, overall equivalent CO2 emissions remain strongly dependent on hydrogen production pathways, with dual-fuel operation offering advantages over full-hydrogen concepts under near-term electricity grid assumptions. Overall, this study demonstrates that dual-fuel aircraft concepts offer a promising intermediate pathway towards aviation decarbonisation, enabling gradual integration of hydrogen while maintaining competitive operational performance.
MSc Thesis